2017
DOI: 10.17265/2161-6264/2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Informal Cross-Border Fish Trade in the Southern Africa Region: A Case of Malawi and Zambia

Abstract: Intra-regional fish trade has potential in addressing the region's food and nutrition insecurity, as well as poverty reduction, by enabling movement of fish from countries of surplus to those with deficit. However, informal fish trade, just like all informal economic activities, has been overlooked and neglected in many national and regional policies, leading to obscurity of such an important part of the fisheries sector. This study examined the situation in the cross-border informal fish trade in order to dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…While the data in our study show a decline in the quantity and number of fish species from December onward, the MP group managed to shift their consumption of fish to dried pelagic species from other freshwater capture fisheries outside of Zambia, which were unaffected by the national fishing ban. Much of this fish is sourced from Malawi or Tanzania [54]. Such fish trade corridors along main roads allowed the MP group to access these fish species and, thus, maintain a higher intake of key micronutrients and omega-3 fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…While the data in our study show a decline in the quantity and number of fish species from December onward, the MP group managed to shift their consumption of fish to dried pelagic species from other freshwater capture fisheries outside of Zambia, which were unaffected by the national fishing ban. Much of this fish is sourced from Malawi or Tanzania [54]. Such fish trade corridors along main roads allowed the MP group to access these fish species and, thus, maintain a higher intake of key micronutrients and omega-3 fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…The research illuminated substantially greater volumes of fish and employment (i.e., compared to FAO statistics and national accounts) associated with cross-border trade, evaluated the impacts of existing policies, and exposed policy myth about the perceived (low) value of the sector and its importance to national and regional economies. The research also showed how informal participants in the sector, particularly women traders, were losing out because of the lack of visibility, regulation, and proper infrastructure (Ayilu et al 2016, Mussa et al 2017. Ultimately, the way in which the research was conducted and reported (i.e., by and to national and regional actors) helped set the agenda for multi-stakeholder dialogue on future policy priorities.…”
Section: Africa Regional Fish Tradementioning
confidence: 95%